2008
DOI: 10.1002/jls.20030
|View full text |Cite
|
Sign up to set email alerts
|

Eldercare and job productivity: An accommodation analysis

Abstract: Over the next decade, the number of working adults relegated to the role of caregiver for one or more elderly family members will rapidly surge. The emotional, physical, and financial stress of caregiving has already begun to impact the productivity of the employee elder caregiver in the workplace, with estimates placing the annual costs around $30 billion. We can expect costs to grow as workers and their elderly parents continue to age. This particular study addresses the fundamental research question of what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(124 reference statements)
0
6
0
2
Order By: Relevance
“…Wagner and Neal (1994), Scott and colleagues (2006), and Sherman and Reed (2008) demonstrated that stress from work and eldercare responsibilities was related to decreased work performance. Wagner and Neal (1994), Scott and colleagues (2006), and Sherman and Reed (2008) demonstrated that stress from work and eldercare responsibilities was related to decreased work performance.…”
Section: Employed Caregivers' Stress Work Interruptions and Work Pementioning
confidence: 99%
“…Wagner and Neal (1994), Scott and colleagues (2006), and Sherman and Reed (2008) demonstrated that stress from work and eldercare responsibilities was related to decreased work performance. Wagner and Neal (1994), Scott and colleagues (2006), and Sherman and Reed (2008) demonstrated that stress from work and eldercare responsibilities was related to decreased work performance.…”
Section: Employed Caregivers' Stress Work Interruptions and Work Pementioning
confidence: 99%
“…Par ailleurs, des études suggèrent que le fait d'être en emploi contribue à diminuer les tensions liées au rôle de proche aidant, plutôt que de les accentuer (Reid et al, 2010). Il semble également qu'avec un soutien adéquat en milieu de travail, les conséquences négatives du rôle de proche aidant sur le rôle d'employé s'estompent (Kossek et al, 2001 ;Sherman et Reed, 2008 ;Zacher et Schultz, 2015;Bowling, 2007). Ainsi, que peuvent faire les employeurs pour remédier à cette situation ?…”
Section: Le Soutien Organisationnel Aux Employés Proches Aidantsunclassified
“…Pourtant, l'emploi constitue une ressource importante pour ces individus en leur permettant, outre l'aspect financier, de faire l'expérience de succès personnels qui les valorisent en dehors de leur rôle d'aidant (Krisor et Rowold, 2014;Robison et al, 2009). Par ailleurs, les entreprises ont le pouvoir de réduire les conséquences organisationnelles négatives liées au rôle de proche-aidant de leurs employés : les proches-aidants qui perçoivent que l'organisation, le supérieur et les collègues comprennent et soutiennent leur situation tendent à vivre moins de tensions (Plaisier et al, 2014;Sherman et al, 2008;Zacher et Schultz, 2015;Zacher et Winter, 2011;Zuba et Schneider, 2013). Cependant, Greenhaus, Ziegert et Allen (2012) suggèrent que le soutien social le plus efficace pour réduire les conséquences négatives du conflit travail-famille est celui qui combine au soutien du supérieur le soutien du conjoint dans la sphère privée.…”
Section: Les Couts Des Responsabilites De Soinunclassified